Development of Pretest-Posttest Assessment Based on Coffee Peel Utilization Project to Measure Students Creative Thinking Skills - Erviana, Lucia; Diawati, Chansyanah; Fadiawati, Noor (FKIP Universitas Lampung, 2022)
This study aims to develop a project-based pretest-posttest assessment of the use of coffee husks. This study used the research and development method of the ADDIE model until the development stage. At the analysis stage, a literature study and a preliminary study were conducted. At the design stage, planning and preparation of an initial draft in the form of a pretest-posttest assessment were carried out. In the development stage, two science education experts validated the suitability of the content and construction of the pretest-posttest assessment with Torrance's creative thinking skills indicator framework. The product of the validation results was then responded to the suitability of the content and construction aspects of creative thinking skills indicators by the three science teachers. The results of expert validation and teacher responses indicated that the pretest-posttest assessment instrument product is very suitable to be used to measure students' creative thinking skills in integrated learning based on coffee peel utilization projects.Keywords: pretest-posttest assessment, coffee peel utilization projects, creative thinking. DOI: http://dx.doi.org/10.23960/jpmipa/v23i1.pp13-24